Evaluation of the health impact of an urban regeneration policy: Neighbourhood Renewal in Northern Ireland. Issue 9 (7th August 2017) - Mohan, Gretta; Longo, Alberto; Kee, Frank
Abstract : Background: Neighbourhood Renewal (NR) was launched in Northern Ireland (NI) in 2003 to revive the social, economic and physical fabric of 36 deprived communities, characterised by a legacy of sectarian conflict. This study evaluates the impact of the policy on health over a decade. Methods: A merged panel of secondary data from the British Household Panel Survey (2001–2008) and Understanding Society (2009–2012) yields longitudinal information on respondents for 12 years. We conducted a controlled before and after investigation for NR intervention areas (NRAs) and three control groups—two groups of comparably deprived areas that did not receive assistance and the rest of NI. Linear difference-in-difference regression was used to identify the impact of NR on mental health, self-rated health, life satisfaction, smoking and exercise. Subgroup analysis was conducted for males and females, higher and lower educated, retired, unemployed and home owner groups. Results: NR did not have a discernible impact on mental distress. A small, non-significant trend towards a reduction in the gap of good self-rated health and life satisfaction between NRAs and controls was observed. A 10% increase in probability of rating life as satisfying was uncovered for retirees in NRAs compared with the rest of NI. Smoking in NRAs declined on par with people from control areas, so a NR influence was not obvious. A steady rise in undertaking weekly exercise in NRAs compared with controls was not statistically significant. Conclusions: Area-based initiatives may not achieve health gains beyond mainstream service provision, though they may safeguard against widening of health disparities.